Electrochemical Behaviors of Glucose Oxidase Based on Biocatalytic Deposition of Gold Nanoparticles. Issue 6 (2nd April 2013) - He, Yaping; Zheng, Jianbin
Abstract Coupling nanotechnology with biocatalysis, a highly sensitive glucose biosensor for the study of electrochemical behaviors of glucose oxidase (GOx) was proposed by using monkshoodvine root–bark like carbon (MLC) as the platform for the biocatalytic deposition of AuNPs. The biosensor showed a linear range from 0.25 to 130 μM with a detection limit of 0.1 μM (S/N = 3) towards glucose and sensitivity of 3010 μA/mM. K appM<inline-graphic xlink:href="ark:/27927/pgg21fvpmb4" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> value was calculated to be 67.4 μM. Furthermore, the proposed AuNPs/GOx–MLC modified pyrolytic graphite electrode (AuNPs/GOx–MLC/PGE) achieved direct electron transfer of GOx. Γ* was calculated to be 2.79 × 10−11 mol/cm2 and ks was 1.79 s−1. It also showed a remarkable electrocatalysis towards glucose.